2018
DOI: 10.1007/s00412-018-0679-4
|View full text |Cite
|
Sign up to set email alerts
|

Chromothripsis, a credible chromosomal mechanism in evolutionary process

Abstract: The recent discovery of a new class of massive chromosomal rearrangements, occurring during one unique cellular event and baptized "chromothripsis," deeply modifies our perception on the genesis of complex genomic rearrangements, but also, it raises the question of the potential driving role of chromothripsis in species evolution. Analyses of the etiology of chromothripsis have led to the identification of various cellular processes capable of generating chromothripsis, such as premature chromosome condensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…These break sites are then repaired in a random manner. While this process is well known, the mechanisms involved in this process are poorly understood (13,63). In our experiments, we observed that similar events take place during DSBs repair (step 3 in Fig.…”
Section: Discussionsupporting
confidence: 59%
“…These break sites are then repaired in a random manner. While this process is well known, the mechanisms involved in this process are poorly understood (13,63). In our experiments, we observed that similar events take place during DSBs repair (step 3 in Fig.…”
Section: Discussionsupporting
confidence: 59%
“…It is well known that the micronucleus frequency is associated with cancer risk in humans, but, e.g. chromothripsis (and probably also other ways for genome reorganization) may also play an important role in species evolution, when occurring in germline cells (Bonassi et al 2007 ; Pellestor and Gatinois 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization between two C. neglecta-like genomes with seven (n 5 7, N 7 ) and six (n 5 6, N 6 ) chromosomes led to the origin of an auto-allotetraploid C. neglecta-like genome (n 5 13, N 6 N 7 ). The allotetraploid conformations may stimulate chromothripsis occurrence (Ivkov and Bunz, 2015;Fukami et al, 2017;Pellestor and Gatinois, 2019). The evidence that plants can undergo the same extreme chromosome shattering observed in some human cancers and developmental syndromes is rather scarce and not yet conclusive.…”
Section: Evolution Of Camelina Genomes Was Accompanied By Chromosome Shatteringmentioning
confidence: 99%